A STUDY ON INCOME PATTERN OF RUBBER TAPPERS IN KALKULAM TALUK, KANNIYAKUMARI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
India is the third largest producer of natural rubber with an annual production of 640,000 tones per annum. In the Indian production, Kerala contributes to 85 per cent and Tamil Nadu 4 per cent followed by Tripura1. Tappers are engaged to harvest the natural rubber (latex) and to process it into concentrated rubber latex (Cenex) and rubber sheets of different grades. The other major activities of rubber industries are seed collection, nursery development, sale of rubber trees, regeneration of rubber plantations, field management system, field Supervision, protection and conservation of plantation, employment generation, and factory processing of natural rubber sales. UnderSection 12(3) of the Industrial Disputes Act, 1947 0.5 man day per hectare per day is fixed as a norm. Accordingly every tapper has to tap 270 to 350 rubber trees per day.Thenorms followed by the Government of Tamil Nadu wherever the duties and responsibilities of the categories in both Government and Corporation are equal.